2017
DOI: 10.1016/j.engstruct.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic performance of existing double track railway bridges at resonance with the increase of the operational line speed

Abstract: This article addresses the dynamic behaviour of double track simply supported bridges of short to medium span lengths (10 m < L < 25 m) belonging to conventional railway lines. These structures are susceptible to experience inadmissible levels of vertical vibrations when traversed by trains at high speeds, and in certain cases their dynamic performance may require to be re-evaluated in case of an increase of the traffic velocity above 200 km/h. In engineering consultancies, these structures have been tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…More recently some authors have investigated the resonance phenomena caused by the circulation of periodic forces or masses following either a semi-analytical [21,22] or a numerical approach [23,24,7]. Neverthe-less, in the authors' opinion, regardless of the approach adopted, resonance phenomena caused by a series of periodic loads and the conditions for its maximization or cancellation depending on the free vibration amplitudes left by each single load have not been analysed in the case of orthotropic plates, especially when these separate from ideal well-known conditions i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently some authors have investigated the resonance phenomena caused by the circulation of periodic forces or masses following either a semi-analytical [21,22] or a numerical approach [23,24,7]. Neverthe-less, in the authors' opinion, regardless of the approach adopted, resonance phenomena caused by a series of periodic loads and the conditions for its maximization or cancellation depending on the free vibration amplitudes left by each single load have not been analysed in the case of orthotropic plates, especially when these separate from ideal well-known conditions i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Definition of a bridge catalogueA representative ensemble of double-track, simply-supported pre-stressed concrete girder decks has been designed with the purpose of covering the mechanical properties of most existing bridges belonging to conventional and high-speed railway lines of this typology. Among the different bridge typologies that can be found in short-to-medium span lengths, precast decks composed by double-T girders have been selected due to their low intrinsic torsional stiffness which makes their dynamic behaviour significantly differ from that of a beam-type structure, exhibiting a noticeable contribution of the first torsion and first transverse bending modes to the vertical acceleration response under railway excitation[24]. Even though in new…”
mentioning
confidence: 99%
“…The same strategy can be applied to any type of structure, and can be exploited with special success if the total response is largely governed by the contribution of one single mode. Because this is especially the case when the peak vibration is due to resonance of one particular mode, the single mode approach can be useful in practical applications and has been used by many researchers: the DER and LIR methods rely on the contribution of the fundamental mode of simple beams, 8 a similar approach was also adopted by Yang et al ., 16 some extensive parametric studies have confirmed its suitability under different conditions, 17,18 and recently the approach has been extended to include the soil-structure interaction effect. 19…”
Section: Closed-form Expression Of the (Free) Acceleration Caused By A Series Of Loads: Residual Influence Linementioning
confidence: 99%
“…In addition, due to dynamic action of the vehicle, the vibration of bridges may lead to the fatigue of structure components [6][7][8]. As railway transportation has the characteristics of heavy loads and obvious vehicle-induced vibration, the large structural stiffness and high durability of both overall structure and components are often required [9][10][11]. Flexible hanger, commonly used in highway arch bridges, are limited in the application to railway arch bridges, for the disadvantages of small stiffness, easy corrosion and needing to be replaced.…”
Section: Introductionmentioning
confidence: 99%